2023
DOI: 10.1002/jbt.23309
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the cardioprotective effects of canagliflozin against cisplatin‐induced cardiotoxicity: Role of iNOS/NF‐κB, Nrf2, and Bax/cytochrome C/Bcl‐2 signals

Abstract: Cardiotoxicity is a severe considerable side effect of cisplatin (CDDP) that requires much medical attention. The current study investigates the cardioprotective effects of canagliflozin (CA) against CDDP-induced heart toxicity. Rats were allocated to the control group; the CA group was administered CA 10 mg/kg/day orally for 10 days; the CDDP group was injected with 7 mg/kg, intraperitoneal as a single dose on the 5th day, and the CDDP + CA group. Compared to the CDDP-treated group, CA effectively attenuated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Subsequent to landmark studies demonstrating the cardioprotective effects of SGLT2 inhibitors in HF, numerous in vivo ( Table 2 ) and in vitro ( Table 3 ) studies, starting in 2019, have underscored the cardioprotective roles of SGLT2 inhibitors in mitigating cardiotoxicity induced by various cancer treatments, including DOX, 17 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 sunitinib, 20 trastuzumab, 21 cisplatin, 19 ipilmumab, 54 , 55 ponatinib, 56 and carfilzomib. 57 DOX has received particular attention because of its status as the most cardiotoxic cancer treatment and its widespread use.…”
Section: Sglt2 Inhibitors In Cardio-oncologymentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequent to landmark studies demonstrating the cardioprotective effects of SGLT2 inhibitors in HF, numerous in vivo ( Table 2 ) and in vitro ( Table 3 ) studies, starting in 2019, have underscored the cardioprotective roles of SGLT2 inhibitors in mitigating cardiotoxicity induced by various cancer treatments, including DOX, 17 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 sunitinib, 20 trastuzumab, 21 cisplatin, 19 ipilmumab, 54 , 55 ponatinib, 56 and carfilzomib. 57 DOX has received particular attention because of its status as the most cardiotoxic cancer treatment and its widespread use.…”
Section: Sglt2 Inhibitors In Cardio-oncologymentioning
confidence: 99%
“…Empagliflozin 17 , 20 , 21 , 39 , 40 , 41 , 42 , 43 , 49 , 55 , 56 and dapagliflozin 44 , 45 , 46 , 48 , 50 , 51 , 52 , 53 , 54 , 56 have emerged as the most commonly used SGLT2 inhibitors, followed by canagliflozin. 19 , 57 Notably, no in vivo studies have reported the protective effects of canagliflozin against DOX, with only 1 in vivo study reporting the cardioprotective effects of canagliflozin against cisplatin 19 and an in vitro study demonstrating its efficacy against carfilzomib. 57 In vitro studies involved different types of cardiomyocytes, 21 , 47 as well as human aortic 56 and human umbilical vein endothelial cells.…”
Section: Sglt2 Inhibitors In Cardio-oncologymentioning
confidence: 99%
See 3 more Smart Citations